Asosiasi Pendapatan Rumah Tangga dengan Tingkat Stres pada Lansia - Jayadi, Rudi; Fadilah, Mala; Zailani, Ahmad (Gema Cendekia Institute, 2025)
Elderly individuals are a vulnerable age group prone to experiencing various psychological problems, one of which is stress. The level of stress among the elderly is influenced by multiple factors, including socioeconomic conditions and household income. This study aims to analyze the association between household income and stress levels among the elderly. The research design employed was cross-sectional, involving 150 elderly respondents aged ≥60 years, selected through purposive sampling. Data were collected using a demographic characteristics questionnaire, household income information, and the standard stress measurement instrument, the Perceived Stress Scale (PSS-10). Data analysis was conducted using chi-square tests and logistic regression. The results showed that 64% of elderly individuals in the low-income category experienced moderate to high levels of stress, whereas only 28% of those with middle-to-high income experienced similar conditions. Statistical tests indicated a significant relationship between household income and stress levels among the elderly (p<0.05). Further analysis revealed that elderly individuals with low income had a 2.7 times higher risk of experiencing stress compared to those with higher income. These findings highlight the crucial role of economic factors in the mental health of the elderly. Intervention efforts focusing on improving economic well-being and providing social support are expected to help reduce the stress burden among the elderly population.